1988
DOI: 10.1002/j.1460-2075.1988.tb02852.x
|View full text |Cite
|
Sign up to set email alerts
|

Genes expressed in the brain define three distinct neuronal nicotinic acetylcholine receptors.

Abstract: Four genes encode the related protein subunits that assemble to form the nicotinic acetylcholine receptor (nAChR) at the motor endplate of vertebrates. We have isolated from the chicken genome four additional members of the same gene family whose protein products, termed alpha 2, alpha 3, alpha 4 and n alpha (non‐alpha) probably define three distinct neuronal nAChR subtypes. The neuronal nAChR genes have identical structures consisting of six protein‐coding exons and specify proteins that are best aligned with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(82 citation statements)
references
References 57 publications
0
81
0
1
Order By: Relevance
“…To establish that the cerebellum contained the ␤2, ␤3, and ␤4 subunits as part of a receptor that binds acetylcholine in a nicotine-dependent manner, we performed immunodepletion experiments with antibodies against the three ␤ subunits and with an anti-␣4 subunit antibody. The ␣4 subunit was considered a likely partner in view of its general codistribution with the ␤2 subunit (Nef et al, 1988). Also, our transfection experiments indicated that the ␣4 subunit was the only ␣ subunit that could form a receptor with all three subunits (data not shown).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…To establish that the cerebellum contained the ␤2, ␤3, and ␤4 subunits as part of a receptor that binds acetylcholine in a nicotine-dependent manner, we performed immunodepletion experiments with antibodies against the three ␤ subunits and with an anti-␣4 subunit antibody. The ␣4 subunit was considered a likely partner in view of its general codistribution with the ␤2 subunit (Nef et al, 1988). Also, our transfection experiments indicated that the ␣4 subunit was the only ␣ subunit that could form a receptor with all three subunits (data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…Because the ␣4 and ␤2 subunits are both broadly distributed in the mammalian brain and have been detected in Northern blots of chick cerebellum (Nef et al, 1988), we examined whether these two subunits were coassembled with the ␤3 and ␤4 subunits. Because the colocalization of the ␤3 and ␤4 subunits in rat cerebellum corresponds well with the immunocytochemical distribution of the ␤2 subunit (Hill, 1993), we used a mAb directed against the ␤2 subunit to immunoprecipitate receptor from detergent extracts of synaptosomes made from rat cerebellum.…”
Section: Coassembly Of the ␤3 And ␤4 Subunits In Cerebellummentioning
confidence: 99%
“…Northern blots were hybridized for 16 h at 42°C in 20% formamide, 6x SET, 10 x Denhardt's solution, 0.1% sodium pyrophosphate, 1% SDS, 100 kg/ml denatured herring sperm DNA and = lo6 cpm/ml radiolabeled probe. Final washes were in 1 x SET, 0.1 olo SDS at 55"C. , vertebrate neuronal genes [6,12], vertebrate muscle genes [6,29,30,32].…”
Section: Northern Analysismentioning
confidence: 99%
“…Within the highly conserved aminoterminal half comprising approximately amino acids l-330 [26] the sequence identity with ALS and ARD protein increases to 75% and 52'70, respectively. Homology values of this region between Da2 and subunits of vertebrate neuronal nAChRs range from =52% (for PZsubunits [5,6]) to =59% (for (~2-subunits [6,8]). The homology between Da2 and muscle receptor proteins is significantly lower.…”
Section: Structure Of the Dcx2 Proteinmentioning
confidence: 99%
“…The α2 subunit was among the first non-muscle nAChR subunits to be cloned and heterologously expressed in a functional subtype, with the β2 subunit [3][4][5] . However, studies into α2 subunit containing (α2*) nAChRs were soon overtaken in number by those into other subtypes.…”
Section: Introductionmentioning
confidence: 99%